Enhancement of adsorption and photocatalytic activities of alkaline-based TiO2 nanotubes for experimental and theoretical investigation under FeCl3 and H2O2 - Zulfiqar, M. (Elsevier Ltd, 2021)
Industrial and manufacturing processes are major responsible for water pollution, which has many environmental and health consequences. The development of efficient, green, and eco-friendly photocatalysis process to treat wastewater containing organic contaminants is highly desirable to solve significant water pollution problems. Herein, the photoreactivity of alkaline-based TiO2 nanotubes (TNTs) was investigated to catalyze the decomposition of green oxidants namely ferric chloride (FeCl3) and hydrogen peroxide (H2O2) to harvest free hydroxyl radicals (OHrad) and finally its significance for the remediation of phenol in visible-light irradiation. To our information, this study first reported that alkaline-based TNTs photocatalyst could successfully activate FelC3 and H2O2 and reduced phenol concentration up to 97.63 %. TNTs were prepared via a hydrothermal process in an alkaline environment at 180 Â°C for 24 h and characterized through XRD, TEM, BET surface area, DRS and FTIR analysis. In adsorption mechanism, pseudo-first-order and Type-1 pseudo-second-order kinetics were proved as best owing to an excellent correlation between experimental and theoretical outcomes and highest R2 up to 0.997. Langmuir and Freundlich isotherms were more appropriate models due to their highest R2 up to 0.994. Several thermodynamic parameters as enthalpy =53.84 kJ/mol, entropy = 173.87 kJ/mol K, Gibbs free energy = â51.76 to â58.71 kJ/mol and activation energy =22.17 kJ/mol were recommended that phenol adsorption method is favourable and spontaneous in nature. The rising temperature was more suitable for phenol removal onto alkaline-based TNTs. Â© 2020 Elsevier Ltd